Functional Orientation and Development Prospect of Natural Gas Power Generation in New Power System - Guanjun FU; Fuqiang ZHANG; Peng XIA; Junshu FENG; Jinfang ZHANG (Zhongguo dianli)
Natural gas power generation has the advantages of low emissions, high efficiency, and flexibility. It is an important component and effective power source for building a new power system under the dual carbon goals of reaching carbon emission peak and carbon neutrality. However, there are still problems in China's natural gas power generation development, such as the relatively low gas source guarantee, high fuel costs, and limited key core technologies. At present, disputes about the development of natural gas power generation in the dual carbon process still exist. It is urgent to have a unified understanding and clarify its development orientation and direction. This paper takes the integrated development of natural gas power generation and new energy generation into consideration in the overall planning of the power system. It uses self-developed carbon emission peak and carbon neutrality power planning software packages for optimization analysis and constructs a low-carbon transformation scenario for the power industry with zero carbon as the goal. It analyzes the future development scale and layout of natural gas power generation under the carbon neutrality goal and conducts sensitivity analysis on the uncertainty factors affecting the future scale of natural gas power generation. Based on the model calculation results, the paper establishes quantitative indicators to evaluate the functional role of gas-fired electricity in new power systems and analyzes its functional role in clean electricity supply, power balance, and peak shaving balance in the future. Natural gas power generation still needs moderate development in the future, with new layouts mainly concentrated in the southeast coastal areas and gradually increasing in the central and western regions. In the future, the focus must be on strengthening the coordination of natural gas production, transportation, storage, and sales, improving the pricing mechanism of natural gas and gas-fired electricity, and accelerating the development of core technologies, to give full play to the positive role of natural gas power generation in the construction of new power system.